Acute Noxious Stimulation Modifies Morphine Effect in Serotonergic but not Dopaminergic Midbrain Areas - Bajic, Dusica (2009)
It is poorly understood if and how pain may modify the effect of opioids on neural systems that contribute to reward and addictive behavior. We hypothesized that the activation of ascending dopaminergic and serotonergic nuclei by morphine is modified by the presence of noxious stimulation. Immunohistochemical double-labeling technique with Fos was used to examine if an intraplantar formalin injection, an acute noxious input, changed the effect of morphine on dopaminergic neurons of the ventral tegmental area (VTA), and serotonergic neurons of the dorsal raphe nucleus (DR). Four groups of rats were analyzed: (1) CONTROL injected with normal saline subcutaneously, (2) rats treated with FORMALIN into the hind paw 30 minutes after normal saline injection, (3) rats injected with MORPHINE sulfate subcutaneously, and (4) rats treated with formalin into the hind paw 30 minutes after morphine injection (MORPHINE/FORMALIN). Following morphine injection, there was an increase in the number of dopaminergic neurons in the VTA with Fos immunolabeling. However, noxious stimulation did not detectably change morphine's effect on Fos expression in VTA dopamine neurons. In contrast, the number of serotonergic neurons containing Fos was increased in the morphine/formalin group compared to all other groups and this effect was topographically selective for the dorsal area of the DR at mid rostro-caudal levels. Therefore, morphine's activation of the VTA, which is associated with motivated behavior and reward seeking, appears similar in the context of pain. However, activation of the ascending serotonin system, which influences mood and has the capacity to modify reward pathways, appears different. In addition, these findings reveal interactions between nociceptive signaling and opioids that contrasts with the notion that opioids simply block access of nociceptive signaling to supraspinal structures.